1996
DOI: 10.1021/je960072z
|View full text |Cite
|
Sign up to set email alerts
|

Densities and Vapor−Liquid Equilibria in Binary Mixtures Formed by Propyl Methanoate + Ethanol, +Propan-1-ol, and +Butan-1-ol at 160.0 kPa

Abstract: Densities and excess volumes were determined at 298.15 K for propyl methanoate + ethanol, +propan-1-ol, and +butan-1-ol. The results of those quantities were then correlated to get the concentrations of vapor−liquid equilibrium obtained isobarically at 160 kPa for the same mixtures. Two mixtures show azeotropes:  for propyl methanoate (1) + ethanol (2), x 1 = 0.443 at T = 358.7 K; and for propyl methanoate (1) + propan-1-ol (2), x 1 = 0.762 at T = 368.2 K. The mixtures are thermodynamically consistent, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Most experimental vapor–liquid equilibrium (VLE) data are measured for binary systems, although most industrial processes contain multiple components. , However, accurate and complete multicomponent data sets are rare, even for common, well-defined mixtures. The absence of complete, systematically measured data in the literature places a requirement on thermodynamic models to follow a correlative approach when predicting the thermodynamic properties of multicomponent mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Most experimental vapor–liquid equilibrium (VLE) data are measured for binary systems, although most industrial processes contain multiple components. , However, accurate and complete multicomponent data sets are rare, even for common, well-defined mixtures. The absence of complete, systematically measured data in the literature places a requirement on thermodynamic models to follow a correlative approach when predicting the thermodynamic properties of multicomponent mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no previous studies have systematically considered the VLE of all the different isomers of a single linear ester with a common second component. Extensive studies have been done into the phase behavior and mixing properties of binary mixtures of linear esters with various primary and secondary alcohols as well as with normal alkanes. These studies have adopted a systematic approach in assessing the effect of varying the alkanolic length of the ester while keeping the acidic chain length constant (or vice versa) on the phase behavior of these esters with a common second component. The choice of an n -alkane as the second component allowed these authors to attribute differences in the observed phase behavior to the dilution or concentration of polar effects due to the presence of the nonpolar alkane.…”
Section: Introductionmentioning
confidence: 99%